Enhancing glioblastoma therapy: unveiling synergistic anticancer effects of Onalespib - radiotherapy combination therapy - Uffenorde, Julia; Hariri, Mehran; Papalanis, Eleftherios; Staffas, Annika; Berg, Josefine; Stenerlöw, Bo; Berglund, Hanna; Malmberg, Christer; Spiegelberg, Diana (Frontiers in Oncology, 2025)
BackgroundGlioblastoma (GBM) is the deadliest form of brain cancer, impacting both adults and children, marked by exceptionally high morbidity and mortality rates, even with current standard treatments such as surgery, radiation therapy, and chemotherapy. Therefore, there is a pressing need for new therapeutic strategies to improve survival and reduce treatment side effects. In this study, we investigated the effect of HSP90 inhibition in combination with radiotherapy in established and patient-derived glioblastoma cell lines.MethodsPotential radiosensitizing effects of the HSP90 inhibitor Onalespib were studied in XTT and clonogenic survival assays as well as in tumor-mimicking multicellular spheroid models. Further, migration capacity and effects on protein expression were studied after exposure to Onalespib and radiation using Proximity Extension Assay analysis.ResultsHSP90 inhibition with Onalespib synergistically enhanced the radiosensitivity of glioblastoma cells grown in 2D and 3D models, resulting in increased cell death, reduced migration capacity and activation of the apoptotic signaling pathway. The proteomic analysis of glioblastoma cells treated with Onalespib, radiation, and their combination revealed significant alterations in protein expression profiles, involved in growth signaling, immune modulation pathways and angiogenesis. Moreover, the combination treatment indicated potential for enhancing cell cycle arrest and apoptosis, suggesting promising anti-tumor effects.ConclusionThese findings demonstrate that HSP90 inhibition may be a promising strategy to enhance the efficacy of radiotherapy in the treatment of GBM, potentially leading to improved outcomes for patients battling this challenging disease.